Unfolded protein response in rice (Oryza sativa L.) varieties with different level of salt stress tolerance - Galang Rizki Ramadhan; Sholeh Avivi; Bambang Sugiharto; Wahyu Indra Duwi Fanata (Universitas Gadjah Mada, 2021)
Plants activate the unfolded protein response as part of cellular adaptation, thereby maintaining the endoplasmic reticulum homeostasis during external stresses exposure. In this study, we examined the relationship between the degree of salt tolerance and unfolded protein response-related gene expression in India salt-tolerant Pokkali and INPARI 35 varieties compared to the Indica salt-sensitive counterpart IR64 and INPARI 4 varieties. Our result showed that the salt tolerance of Pokkali and INPARI 35 had been confirmed by their higher survival rate, higher chlorophyll content, lower electrolyte leakage, and lower H2O2 and malondialdehyde content under salt stress conditions. Furthermore, the expression of unfolded protein response genes was highest in INPARI 35, whereas IR64 and INPARI 4 exhibited low gene induction during endoplasmic reticulum stress conditions. Among the four examined varieties the salt tolerant Pokkali surprisingly showed the lowest induction of all examined unfolded protein response-related genes. These results indicated the possibility that unfolded protein response supports the rice plant for adapting to the saline environment.